2014
DOI: 10.1002/2013jd020709
|View full text |Cite
|
Sign up to set email alerts
|

Perturbed physics ensemble simulations of cirrus on the cloud system‐resolving scale

Abstract: In this study, the effect of uncertainties in the parameterization of ice microphysical processes and initial conditions on the variability of cirrus microphysical and radiative properties are investigated in a series of cloud system‐resolving perturbed physics ensemble (PPE) and initial condition ensemble (ICE) simulations. Three cirrus cases representative of midlatitude, subtropical, and tropical anvil cirrus are examined. The variability in cirrus properties induced by perturbing uncertain parameters in ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…It is shown that the combination of the change to the modified Phillips et al (2008) heterogeneous ice nucleation scheme with the introduction of the sedimentation of cloud ice accounts for the largest change in CIWC. This partly agrees with Muhlbauer et al (2014), who identify the number of IN available for heterogeneous freezing, which is controlled by the heterogeneous ice nucleation scheme, as one of the three major uncertainties in microphysical variability. Including cloud ice sedimentation whilst keeping the former modified Fletcher (1962) ice nucleation scheme has a far smaller impact, because the modified Fletcher (1962) scheme produces more numerous but smaller cloud ice crystals, which-due to the sizedependency of their fall speed-sediment slower than the less numerous but larger cloud ice crystals the Phillips et al (2008) scheme produces.…”
Section: Discussionsupporting
confidence: 90%
“…It is shown that the combination of the change to the modified Phillips et al (2008) heterogeneous ice nucleation scheme with the introduction of the sedimentation of cloud ice accounts for the largest change in CIWC. This partly agrees with Muhlbauer et al (2014), who identify the number of IN available for heterogeneous freezing, which is controlled by the heterogeneous ice nucleation scheme, as one of the three major uncertainties in microphysical variability. Including cloud ice sedimentation whilst keeping the former modified Fletcher (1962) ice nucleation scheme has a far smaller impact, because the modified Fletcher (1962) scheme produces more numerous but smaller cloud ice crystals, which-due to the sizedependency of their fall speed-sediment slower than the less numerous but larger cloud ice crystals the Phillips et al (2008) scheme produces.…”
Section: Discussionsupporting
confidence: 90%
“…Using a cloud‐system‐resolving model with two‐moment cloud microphysics scheme, Muhlbauer et al . [] also showed that sulfate aerosol number concentrations available for homogeneous freezing have virtually no effect on the microphysical properties and radiative impact of midlatitude and subtropical cirrus and have only minor effect on tropical anvil cirrus. For midlatitude and subtropical cirrus, the insensitivity of cirrus cloud properties to sulfate aerosol number concentrations is attributed to the fact that cirrus formation in these clouds is dominated by heterogeneous freezing in their simulations.…”
Section: Changes In Anthropogenic Aerosol Forcing From Different Cirrmentioning
confidence: 99%
“…With a time step of 10 s, it is not clear how well the supersaturation is simulated for ice freezing events and further for the effects of sulfate aerosol number concentrations on simulated cirrus cloud properties in Muhlbauer et al . []. The discrepancy between this study and some other studies is now being further investigated with cloud parcel models under a variety of conditions such as sulfate aerosol size distribution, updraft velocity, numerics, etc.…”
Section: Changes In Anthropogenic Aerosol Forcing From Different Cirrmentioning
confidence: 99%
“…While using COSP facilitates a more consistent comparison between model output and satellite data, differences between the model simulation and the satellite can, for example, still arise due to displacements in simulated storm tracks. COSP has previously been used with COSMO by Mühlbauer et al (2014Mühlbauer et al ( , 2015. The output diagnostics include a variety of cloud properties, which facilitate consistent model-to-observation comparisons as well as consistent intermodel comparisons.…”
Section: Model Evaluation Methodsmentioning
confidence: 99%